Classroom Management for Physical Education Teachers in Babylon Governorate - Alaa Jabbar Abed Nassar; Mohamed Abdel-Sadah Hassan (Institute of Medico-legal Publications Pvt Ltd, 2021)
The importance of the study lies in the fact that it carries a purposeful mission that seeks to study classroommanagement with physical education teachers in Babylon Governorate by making use of what he possessesfrom appropriate teaching experience in order to benefit from it in directing material and human potentialsbecause of its great impact on the quality of the educational process, as the researchers hope for during thisstudy and its results, the educational institutions benefited in particular.As for the research problem, through the researchers’ experience in the educational field, they noticedthat there is a lag in the classroom management process by some male and female teachers through poorconsideration of the psychological and social aspects and individual differences of students, which areimportant factors for the success of the classroom management process.While the objectives of the research were to build the classroom management scale for physical educationteachers in Babil Governorate, as well as to identify the reality of classroom management among physicaleducation teachers from the point of view of school administrations. The researchers used the descriptiveapproach to solve the research problem due to its suitability to the nature of the study, and on the mainresearch sample of (120) sports education schools in Babylon Governorate, after extracting the results andtreating them with appropriate statistical means.